Recent advances in functional design of nanocellulose and their intelligent application - Yan Lv; Qian Li; Weidong Yang; Zhen Zhang; Yan Li (International Journal of Smart and Nano Materials)
Environmental pollution is a serious global challenge, and nanocellulose, as an emerging bio-based functional material, offers novel perspectives for addressing this issue. As an abundant and sustainable material, nanocellulose exhibits properties such as high strength, high modulus, light weight, surface rich in functional groups, and biodegradability. These properties allow it to be chemically or physically modified to confer conductivity, magnetism, or other functionalities, thus showing great promise in the development of self-adaptive materials. This paper reviews the latest advancements in the diverse production of nanocellulose-based self-adaptive materials across various dimensions and their applications in intelligent scenarios from the perspective of diversified functional materials production. It begins with a concise overview of the preparation methods and structural features of different types of nanocellulose. Subsequently, it introduces the preparation of one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) nanocellulose-based functional materials through assembly, integration, and specific structural design. Following this, the applications of nanocellulose-based materials of different dimensions in self-adaptive product fields such as sensors, actuators, supercapacitors, flexible electrodes, drug delivery, and electromagnetic shielding. Finally, the paper provides insights into the prospects and challenges of these products in smart applications and proposes feasible solutions.